"Our Answer for Obama": The Logic of Symbolic Aggression. Issue 3 (3rd July 2020) - Arkhipova, Alexandra S.; Radchenko, Daria A.; Titkov, Alexey S.
ABSTRACT: The article analyzes forms of vernacular response to the economic sanctions against Russia introduced in 2014. Reactions, expressed in verbal and visual texts, differ by the degree to which participants are involved—from a clichéd individual expression to a collective event—and by the level of symbolic aggression embedded in them. In the course of 2014–15, a shift is observed from speech clichés not addressed to the opponent directly to more aggressive texts and practices. This shift is connected with the loss of popularity of earlier forms of vernacular reaction to the sanctions and the situation stemming from them.